2018
DOI: 10.1016/j.molcel.2018.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Degradation Signals and Pathways in a Eukaryotic N-terminome

Abstract: Most eukaryotic proteins are N-terminally acetylated. This modification can be recognized as a signal for selective protein degradation (degron) by the N-end rule pathways. However, the prevalence and specificity of such degrons in the proteome are unclear. Here, by systematically examining how protein turnover is affected by N-terminal sequences, we perform a comprehensive survey of degrons in the yeast N-terminome. We find that approximately 26% of nascent protein N termini encode cryptic degrons. These degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
100
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(118 citation statements)
references
References 105 publications
6
100
0
Order By: Relevance
“…Another plausible explanation for the stabilization of PLIN2 on LD most likely stems from the spatial segregation between LD-anchored PLIN2 and ER-embedded TEB4, which would prevent the interaction of the Ac/N-degron of PLIN2 with TEB4 E3 Ub ligase. Nonetheless, we cannot exclude the possibility that TEB4 is still in proximity to the PLIN2 protein, and targets it for degradation while LD is budding from ER membrane, as Doa10 (a counterpart of TEB4 in S. cerevisiae) regulates the abundance of the LD-associated proteins during LD biogenesis from the ER (39).…”
Section: Discussionmentioning
confidence: 99%
“…Another plausible explanation for the stabilization of PLIN2 on LD most likely stems from the spatial segregation between LD-anchored PLIN2 and ER-embedded TEB4, which would prevent the interaction of the Ac/N-degron of PLIN2 with TEB4 E3 Ub ligase. Nonetheless, we cannot exclude the possibility that TEB4 is still in proximity to the PLIN2 protein, and targets it for degradation while LD is budding from ER membrane, as Doa10 (a counterpart of TEB4 in S. cerevisiae) regulates the abundance of the LD-associated proteins during LD biogenesis from the ER (39).…”
Section: Discussionmentioning
confidence: 99%
“…The tFT reports on protein stability independently of expression through the intensity ratio of the slow maturing mCherry and the fast maturing sfGFP fluorescent proteins, which increases as a function of protein half-life in steady state (Khmelinskii et al, 2012;Khmelinskii et al, 2016). In the course of that study we observed that reporters with a proline residue immediately following the ubiquitin moiety (Ubi-PZ-tFT reporters) exhibited increased turnover in strains lacking the N-terminal acetyltransferase NatA ( Fig 1A), whereas no destabilization was observed in NatB and NatC mutants (see Supplementary Figure S3 in (Kats et al, 2018)). The N-terminal ubiquitin moiety is usually co-translationally cleaved by endogenous deubiquitinating enzymes (DUBs) (Bachmair et al, 1986), which enables the exposure of non-native amino acid residues at the N-terminus of the reporter protein.…”
Section: Nata Affects Turnover Of Ufd Substratesmentioning
confidence: 85%
“…The protein stability index (PSI) is a measure of protein turnover resulting from high-throughput analysis of tFT-tagged constructs and increases as a function of the mCherry/sfGFP ratio and is therefore anticorrelated with degradation rate. Data from Kats et al (Kats et al, 2018). Boxplots show median, 1 st and 3 rd quartile, whiskers extend to ± 1.5x interquartile range (IQR) from the box.…”
Section: Nata Affects Turnover Of Ufd Substratesmentioning
confidence: 99%
See 2 more Smart Citations